IMPLEMENTATION OF STEAM (Science Technology Engineering Art Mathematics) - BASED EARLY CHILDHOOD EDUCATION LEARNING IN SEMARANG CITY - Muniroh Munawar; Fenny Roshayanti; Sugiyanti Sugiyanti (IKIP Siliwangi, 2019)
Learning in Early Childhood Education (ECE) today should adjust the 21st century competency framework. In this case, learning innovation is needed to actualize a generation that is creative, innovative, critical thinking, able to communicate and collaborate. STEAM (Science Technology Engineering Art Mathematics) - based ECE learning is currently seen as an approach that aims to stimulate creativity and prepare children in a world of work that is full of innovation and invention. Research shows that there is a positive relationship between STEAM experience at early age and school success in the future. The purpose of this study is to describe the implementation of STEAM-based ECE learning in Semarang City. Three ECE schools that have implemented STEAM-based learning in Semarang City were included as research subjects. The research methods used were qualitative with observation, interview and documentation as a data collection technique. The research focus of the research results include: 1) Story times in STEAM class, 2) STEAM Processes in learning, 3) STEAM activities in class. Data analysis results show that the implementation of STEAM-based learning is not fully integrated, so assistance by expert teams is needed and there is no comprehensive learning media tool.Pembelajaran di PAUD sekarang ini hendaknya menyesuaikan kerangka kompetensi abad 21, dimana inovasi pembelajaran sangat dibutuhkan untuk mewujudkan generasi yang kreatif, inovatif, berpikir kritis, mampu berkomunikasi dan berkolaborasi. Akhir-akhir ini STEAM (Science Technology Engineering Art Mathematics) dipandang sebagai sebuah pendekatan untuk menyiapkan generasi abad 21, yang bertujuan untuk menstimulasi kreativitas, menyiapkan anak-anak dalam dunia kerja yang penuh inovasi dan invensi. Riset menunjukkan bahwa ada hubungan positif antara pengalaman STEAM di awal usia dengan kesuksesan sekolah di masa mendatang. Adapun tujuan penelitian ini adalah untuk mendeskripsikan pelaksanaan pembelajaran STEAM di PAUD. Metode penelitian yang digunakan adalah kualitatif, pengumpulan data dilakukan melalui observasi, wawawancara dan dokumentasi. Sedangkan hasil penelitian ini mendeskripsikan: 1) Storytimes dalam kelas STEAM, 2) STEAM Process dalam pembelajaran, 3) Aktivitas STEAM di kelas. Hasil analisis data menunjukkan bahwa implementasi pembelajaran berbasis STEAM tidak sepenuhnya terintegrasi, sehingga diperlukan bantuan oleh tim ahli dan tidak ada alat media pembelajaran yang komprehensif.